2018
DOI: 10.1590/1807-1929/agriambi.v22n2p107-112
|View full text |Cite
|
Sign up to set email alerts
|

Marketable yield of onion under different irrigation depths, with and without mulch

Abstract: A B S T R A C TThe objectives of this study were to obtain the onion crop coefficients and evaluate the influence of different irrigation depths (0, 22, 45, 75 and 100% of crop evapotranspiration) on marketable yield and quality of onion bulbs cultivated with and without mulch of elephant grass. The experiment was carried out in Seropédica, RJ, Brazil, from May to September 2012, in a Red Yellow Argisol. The experimental design was in randomized blocks in split plots, with 10 treatments and seven replicates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
(20 reference statements)
0
6
0
5
Order By: Relevance
“…The use of dead vegetation cover under water/salt stress conditions presents itself as an alternative to soften temperature fluctuation, maintaining soil moisture and consequently promoting the dilution of salts in the soil solution (BARBOSA et al, 2021;CARVA L HO;RIBEIRO;GOMES et al, 2018), reducing the osmotic and toxic effects associated with excess of salts in the root zone on the physiological and biochemical functions of plants (LACERDA et al, 2011;SOUSA et al, 2020). On the other hand, the absence of vegetation cover intensifies the salinity-inhibiting effect on the reproductive efficiency of peanut plants.…”
Section: Resultsmentioning
confidence: 99%
“…The use of dead vegetation cover under water/salt stress conditions presents itself as an alternative to soften temperature fluctuation, maintaining soil moisture and consequently promoting the dilution of salts in the soil solution (BARBOSA et al, 2021;CARVA L HO;RIBEIRO;GOMES et al, 2018), reducing the osmotic and toxic effects associated with excess of salts in the root zone on the physiological and biochemical functions of plants (LACERDA et al, 2011;SOUSA et al, 2020). On the other hand, the absence of vegetation cover intensifies the salinity-inhibiting effect on the reproductive efficiency of peanut plants.…”
Section: Resultsmentioning
confidence: 99%
“…Assim, verificou-se economia no uso da água de 12,3 % com o uso de cobertura do solo com palhada de cana-de-açúcar. Essa economia pode ser explicada pelo fato de a palhada proporcionar uma depleção mais lenta da água no solo em consequência da redução da evaporação da água da superfície, manutenção umidade e redução da temperatura do solo (SANTOS et al, 2012e CARVALHO et al, 2018 e redução da incidência de plantas daninhas (SILVA et al, 2009) Irr. v. 13, nº 1, Fortaleza, p. 3236 -3246, Jan-Fev, 2019 possibilitar aumento do turno de rega e aplicação de menor quantidade de água durante o ciclo da cultura, além de favorecer a redução dos custos operacionais da irrigação.…”
Section: Resultsunclassified
“…Daily variations of Kc for the three treatments were described by decreasing quadratic polynomials, which indicate maximum points between 1200 and 1300 degree-days and maximum Kc values lower than 0.60. Recently, various studies on the interaction between mulching and irrigation indicated that the use of mulch allows the application of lower irrigation depths, leading to crop coefficients lower than that for cultivation in bare soil (Carvalho et al, 2016(Carvalho et al, , 2018.…”
Section: Resultsmentioning
confidence: 99%